The 3D Sound Power of Immersion Processing and Psychophysiological Effects of Binaural versus Stereo Audio Stories. - Rodero, Emma; Rodríguez-de-Dios, Isabel (Media Psychology, 2024)
Many people are listening to fiction stories in podcasts and audiobooks. Some techniques, such as 3D or binaural sound, might improve the listeners' sensory experience in this kind of format. However, few audio productions are produced with binaural sound, and research about their effects on cognitive processing is scarce. Therefore, this study aims to analyze the impact of binaural sound in audio stories compared to their stereo versions on the listeners' cognitive processing and physiological responses. Fifty participants listened to two stories produced in two versions: binaural and stereo, and they assessed enjoyment, engagement, and imagery while their physiological responses were measured (heart rate and electrodermal activity). Also, they performed a recognition test. The results showed that the binaural version achieved higher narrative engagement, enjoyment, imagery, and information recognition than the stereo stories. The psychophysiological responses indicated the highest attention and arousal in binaural stories.